Acute on chronic liver failure from novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). (20th May 2020) - Qiu, He; Wander, Praneet; Bernstein, David; Satapathy, Sanjaya K.
Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a highly infectious viral disease that predominantly causes respiratory symptoms. Elevated liver enzymes have been reported during the course of disease and appear to be common. We present a 56‐year‐old woman with a history of decompensated alcoholic cirrhosis who presented with abdominal pain, fever and diarrhoea and was found to have acute on chronic liver failure secondary to SARS‐CoV‐2 infection. The patient was treated with empiric antibiotic and supportive care with subsequent improvement.